Higher-order transient structures and the principle of dynamic connectivity in membrane signaling - Yuxi Zhang; Roderick MacKinnon (Proceedings of the National Academy of Sciences, 2025)
We examine the role of higher-order transient structures (HOTS) in M2R regulation of GIRK channels. Electron microscopic membrane protein location maps show that both proteins form HOTS that exhibit a statistical bias to be near each other. Theoretical calculations and electrophysiological measurements suggest that channel activity is isolated near larger M2R HOTS. By invoking weak interactions that permit transient binding of M2R to M2R and GIRK to GIRK ( i-i interactions) and M2R to GIRK ( i-j interactions), the distribution patterns and electrophysiological properties of HL-1 cells are replicated in a reaction-diffusion simulation. We propose the principle of dynamic connectivity to explain communication between protein components of a membrane signaling pathway. Dynamic connectivity is mediated by weak, transient interactions between proteins. HOTS created by weak i-i interactions, and statistical biases created by weak i-j interactions promoted by the multivalence of HOTS, are the key elements of dynamic connectivity.